Implementasi Penggunaan Website E-Commerce Sebagai Sarana Pemberdayaan Masyarakat pada Kecamatan Pasar Rebo Jakarta Timur - Avip Kurniawan; Herry Wahyono; Nuke L Chusna; Darmawan, Risanto; Mega Wahyu Rhamadani (Yayasan Literasi Sains Indonesia, 2023)
In order to empower the community in Pasar Rebo District, this study concentrates on the e-commerce website platform. It will do this by supplying in-depth details about goods and services, facilitating online transactions for the community, and educating the community so that they can launch an online business. To learn more about how people view and interact with e-commerce websites, this study strategy combines surveys, interviews, and data analysis. This study also examines how e-commerce will affect the economy, including how it will open up new markets for regional goods and whether it would raise people's incomes. The constraints of handwritten information are overcome by this platform through the use of dynamic technologies and database connectivity. There is a need for more efficient access to information, particularly in the One Million Orchid Village Program, in the context of community service activities for the subdistrict, community empowerment through increasing access to information, digital skills, and participation in the digital economy. This study created a responsive and effective display using the E-Commerce framework, guaranteeing consistency and accessibility across different devices. In conclusion, the community can gain more economically and socially by using this technology, fostering a competitive and sustainable environment in Pasar Rebo District, East Jakarta.